FREEDOM OF EXPRESSION AND THE RIGHT TO RESPECT FOR PRIVATE LIFE - Goran Ilic (Srpska Politička Misao)
The paper analyzes the relationship between freedom of expression and the right to respect for honour and reputation. It was pointed out the importance that is given to freedom of expression nowadays, and it was especially considered the practice of the European Court of Human Rights. On that occasion, the difference that exists between public and private personalities was pointed out, as well as the doubts that may arise from the distinction between factual statements and value judgments. When it comes to the right to privacy, the author referred to the importance of honour and reputation, and on that occasion reminded of the “double” presence of these values. In one case it is Art. 10 of the European Convention on Human Rights, and in another the case law of the European Court of Human Rights regarding the meaning of the term of the right to privacy from Art. 8 of the European Convention on Human Rights. Solutions in domestic law and case law are analyzed, and special attention is paid to one case in which the relationship between freedom of expression and violation of honor and reputation was discussed. The specificity of this situation is reflected, inter alia, in the fact that we are talking about university professors. The author used the normative, comparative and historical method when writing the paper.